Apokalipszis most? „...aki igaz, cselekedjék igazságot ezután is...” (Jel 22,11) avagy A filozófus egy puzzle bolygón - Csikai, Ildikó (Kultúratudományi Szemle, 2022)
Apokalypse Now? Ildikó Csikai The critical condition of our planet and the crises of philosophy are not new phenomenons. According to a group of researchers, philosophy also needs a renewal, and not only in the proceed on the ground of evidence-based arguments and critical thinking but also it has to participate effectively in the education process for the birth of action-oriented and socially responsible citizen. The article is looking for answers if philosophy, philosophers can have any roles in the current situation, in the possible solutions of the difficulties of our planet.